Towards a humanistic approach to the Quran: new direction in contemporary Islamic thought - Akbar, Ali (Culture and religion, 2019)
Historically, Muslim orthodoxy has regarded the Quran as God's Word dictated to Muhammad through the mediation of the Angel Gabriel, and has thus maintained the corresponding argument that the Prophet played no role in shaping the content of the Quranic revelations. This paper discusses a project of what I shall refer to as 'reforming theology' within contemporary Islamic scholarship which stands in contrast to the dominant orthodox view of revelation and the nature of the Quran. In particular, the paper examines how several contemporary Muslim scholars, namely Fazlur Rahman (from Pakistan), Abdolkarim Soroush and Muhammad Mujtahed Shabestari (from Iran) and Nasr Hamid Abu Zayd (from Egypt), challenge the widely accepted idea about the Quran being the literal Word of God. The paper argues that the project of these scholars represents a radically new direction in Islamic theology because of its strong emphasis on the human side of the Quran. It also shows that the implications of these scholars' re-examination of traditional theories of revelation are not only limited to theological matters, or specifically the communicative relationship between God and His Prophet, but also have a number of consequences for the practice of exegesis.